1719. Pharmacokinetics (PK) of Oritavancin in Children: The ORKIDS Trial. (26th November 2018) - Bradley, John; Arrieta, Antonio; Bokesch, Paula; Fusaro, Karen; Griffith, David C; Loutit, Jeffrey S
Abstract: Background: Oritavancin (ORI) is a lipoglycopeptide antibiotic approved in adults as a single 1, 200 mg intravenous (IV) dose for the treatment of acute bacterial skin and skin structure infections (ABSSSI) caused by Gram-positive organisms, including methicillin-resistant Staphylococcus aureus . The objective in children is to achieve a PK profile that is similar to that attained in adults. PK and safety data from the first 3 age-specified cohorts are presented. Methods: The ORKIDS trial is a Phase 1 open-label, sequential, dose-finding study evaluating the PK, safety and tolerability of a single-dose 15 mg/kg (max 1, 200 mg) IV infusion of oritavancin in children under 18 years. The first 3 age cohorts (12 to <18 years, 6 to <12 years, 2 to < 6 years) with 8 subjects in each cohort have completed the study. Subjects were required to have a suspected or confirmed Gram-positive bacterial infection for which they received standard-of-care antibiotic therapy. Following a single dose of ORI, PK samples were obtained at 3, 4, 9, 24, 48, 72, and 336 hours after the start of the 3-hour infusion. Plasma concentrations were analyzed by noncompartmental Methods. Subjects were evaluated for safety through Day 60. An independent data safety monitoring board evaluated the safety and PK data of each cohort prior to dosing the subsequent cohort. Results: PK in children compared with adult data from the SOLO Phase 3 ABSSSI studies (Table 1). Conclusion: In subjects 6 to <18 years, a single 15 mg/kg dose of ORI appears to be well tolerated and provides a PK profile similar to a single 1, 200 mg dose in adults. Mean AUC0-inf of 1, 963 h μg/mL in subjects 2 to <6 years is lower than the targeted exposure range in adults. A higher dose of ORI is currently being studied in this cohort. Disclosures: J. Bradley, Melinta Therapeutics: Investigator, Research support. A. Arrieta, Melinta Therapeutics: Investigator, Research support. P. Bokesch, Melinta Therapeutics: Consultant, Consulting fee. K. Fusaro, Melinta Therapeutics: Employee, Salary. D. C. Griffith, Melinta Therapeutics: Consultant, Consulting fee. J. S. Loutit, Melinta Therapeutics: Consultant, Consulting fee.